Palinología de la Formación Chiquimil (Mioceno Superior), en Río Vallecito, provincia de Catamarca, Argentina. Parte 3. Polen (Ameghiniana, 2014)
Systematic descriptions of 33 angiosperm pollen species from the Chiquimil Formation at Río Vallecito are presented. Two species are emended: Rhoipites atoeolaius (Couper) Pocknall and Crosbie, and R. baculaius Archangelsky and two new combinations are proposed: Tubulijíoriditc« spinosus Hammen ex Germeraad, Hopping and Muller and T. minutus Regali, Uesugui and Santos. In addition the following species: Periporopollenites uesicus Partridge, Parsonsidites muliiporus Mildenhall and Crosbie, Rhoipites alueolatus (Couper) Pocknall and Crosbie, R. exiguus Pocknall, R. karamuensi « Pocknall, R. fmgilis Mildenhall and Pocknall, Tnbuíijlondñcs minutus Regali, Uesugui and Santos, Pauieocoprosnuuiites zeiandiae Pocknall, Psilatricolporites cyanllls Hammen and Wijmstra, Tetracolporopollenite « lllegndolilll1l (Potonié) Frederiksen and PolycolpJropollenites esobalieus (McIntyre) Pocknall and Mildcnhall me recorded for Argentina for the first time. In the pollen assemblages of Río Vallecito 90 species ha ve been recognised, having most of them a wide distribution in Gondwana.